2007
DOI: 10.1111/j.1365-2494.2007.00570.x
|View full text |Cite
|
Sign up to set email alerts
|

Mineral concentrations in herbage and soil in a Pinus radiata silvopastoral system in north‐west Spain after sewage sludge and lime application

Abstract: Summary Silvopastoral systems in north‐west Spain can reduce the risk of fires and promote multi‐purpose forest land use. Fertilizer application is important for optimal pasture and tree production. The application rate of sewage sludge as a fertilizer is regulated and is based on its nutrient concentration, especially nitrogen. The aim of this study was to assess the effect of three consecutive years of application of different application rates of sewage sludge and inorganic fertilizer, with or without lime … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…To this end, the effect of sewage sludge on plant and tree growth, pasture botanical composition, in-soil macronutrient levels (N, P, K, Ca and Mg), and pasture quality (crude protein, P, K, Ca and Mg) in silvopastoral systems in very acidic soils in 5-8-year-old plantations has already been evaluated Rigueiro-Rodríguez et al, 2007). It was shown that sewage sludge application in acid soils initially increases soil pH, simultaneously reducing aluminium saturation in the interchange complex and increasing macronutrient availability .…”
Section: Introductionmentioning
confidence: 99%
“…To this end, the effect of sewage sludge on plant and tree growth, pasture botanical composition, in-soil macronutrient levels (N, P, K, Ca and Mg), and pasture quality (crude protein, P, K, Ca and Mg) in silvopastoral systems in very acidic soils in 5-8-year-old plantations has already been evaluated Rigueiro-Rodríguez et al, 2007). It was shown that sewage sludge application in acid soils initially increases soil pH, simultaneously reducing aluminium saturation in the interchange complex and increasing macronutrient availability .…”
Section: Introductionmentioning
confidence: 99%
“…In Galicia, the natural soils have low fertility due to their acidity (Zas and Alonso, 2002). This acidity implies a high concentration of saturated aluminium in the exchange complex and low cation and phosphorus availability (Prasad and Power, 1997; Rigueiro‐Rodríguez et al. , 2007).…”
Section: Introductionmentioning
confidence: 99%
“…We have evaluated the effects of sewage sludge on pasture production, pasture botanical composition and macronutrient levels in soil (N, p, K, Ca and Mg) and pasture (crude protein, p, K, Ca and Mg) in silvopastoral systems established under a 5-year-old Pinus radiata d. don plantation in north-west Spain in previous studies (Mosquera-Losada et al 2001;López-díaz et al 2007;Rigueiro-Rodríguez et al 2007). in these studies, it was shown that sewage sludge application in acid soils increases soil pH and, therefore, it reduced aluminium saturation in the interchange complex (López-díaz et al 2007), causing an increase of sown species presence in pasture and, usually, improving pasture quality and productivity (López-díaz et al 2007;Rigueiro-Rodríguez et al 2007).…”
Section: Introductionmentioning
confidence: 99%